Gastrointestinal Tumors Mimicking Adnexal Masses: A Report of Three Cases and Review of the Literature - Berna Dilbaz; Burak Karadağ (Gynecology Obstetrics & Reproductive Medicine)
It is important to determine the origin and malignancy risk of pelvic pathologies preoperatively and thus decide the route and extent of the surgery. In this case report, we present three cases operated for presumed adnexal masses those were intraoperatively diagnosed to be nongynecological benign masses originating from adjacent organs with a brief review of the literature. Three cases underwent surgery with a pre-operative diagnosis of adnexal mass but intraoperatively diagnosed to be mucinous cystadenoma of appendix, mesenteric cyst and gastrointestinal stromal tumor. Non-gynecological masses should be considered in the differential diagnosis of adnexal masses and centers operating on a considerable number of adnexal masses should be capable of managing rare nongenital masses that can be accidentally encountered during the operation.